NUMERICAL STUDY ON CHARACTERISTICS OF NATURAL, FORCED AND COMBINED CONVECTION HEAT TRANSFER ON SUB CHANNEL WITH SQUARE CYLINDER ARRANGEMENT - CIPTADI SYURYAVIN (NIM : 24908008); Pembimbing 1 : Prof. Dr. Ir. Aryadi Suwono; Pembimbing 2, AHMAD
Heat transfer occurs in a nuclear reactor core covering natural, forced or combined convection. The existence of natural, forced and combined convection in reactor extremely defines reactor safety system itself. By studying the natural, forced and combined convection we can obtain the safety limits, such as power, coolant flow rate and temperature of nuclear reactor coolant. In general, correlation equations especially for natural convection is still very low in availability and the experiment’s result has limited accuracy. This research is focused in observing the characteristics of natural, forced or combined convective heat transfer at a vertical sub channel with square lattice arrangement of cylinders using FLUENT 6.3 computer software. This research is done to find forced, natural and combined convection correlation equations in square lattice sub channels. The correlation equations obtained will be compared with Joko Supriyadi’s experiment. Numerical simulation conducted in this study also uses the same test model that is used in Joko Supriyadi’s experiment.